A Diffraction Ray Tracing Method Based on Curved Surface Ray Tube for Complex Environment - Dan Shi; Na Lv; Yougang Gao , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A self-adaptive ray tracing method for predicting radio propagation based on the curved surface ray tube (CSRT) model is proposed in this paper. The CSRT model is implemented in the ray tracing method to reduce the unnecessary consume compared with the four-ray tube model in complex environments. Both the theoretical calculation and the practical simulation were applied to verify the high efficiency of the CSRT model. The radio wave propagation in a complex scene was calculated by the CSRT model and the four-ray tube model, and the theoretical analytical result demonstrated that the CSRT model achieved a speed up of 4 times compared to the four-ray tube model. Moreover, the wave propagations in several different environments were simulated with our developed software based on the CSRT and four-ray tube tracing method, and the comparisons of the simulation time spent by the two methods proved the high efficiency of the CSRT model. In addition, the correct prediction of the propagation paths and E-field also validates the accuracy of the CSRT model.